Using the unemployed as temporary employment counsellors: Evaluation of an initiative to combat longterm unemployment - Lennart Delander; Jonas Månsson; Erik Nyberg (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2004)
This study investigates empirically the effects of a pilot project in which unemployed persons were used as temporary employment counsellors. Economic theory clearly points in the di-rection of a positive relation between search intensity and exit from unemployment. The fundamental concept of the project was the use of unemployed, who underwent customised training, to assist other unemployed in their job search. The project was carried out during a period in which the caseload was very high at public employment offices, which resulted in a drastic reduction in individual placement services available to the unemployed. It was based on a collaboration agreement between trade union confederations and the Swedish Labour Market Administration. Based on individual records drawn from administrative data, this paper examines the impact of the project on the probability of being removed from the live register of the Employment Service (various reasons for being removed are analysed separately) or being placed in a labour market policy programme. For job seekers placed in such programmes, the evaluation also examines effects on the probability of gaining employment within a given time period subsequent to programme participation. The impact on the period of time from the start of the project until a job seeker is removed from the register or placed in a labour market policy programme is also examined. The estimated effects indicate that the project had a positive impact on job search effectiveness and, thereby, in its efforts to reduce long periods out of work. – – Die vorliegende Studie ist eine empirische Untersuchung der Auswirkungen eines Pilotpro-jektes, bei dem Arbeitslose vorübergehend als Arbeitsberater eingesetzt wurden. Wirtschaftstheorien sehen einen positiven Zusammenhang zwischen der Intensität der Su-che nach einem Arbeitsplatz und dem Austritt aus der Arbeitslosigkeit. Das grundlegende Konzept des Projektes lag im Einsatz von Arbeitslosen, die nach einer kundenorientierten Schulung anderen Arbeitslosen bei ihrer Arbeitssuche assistierten. Zeitlich angesiedelt wur-de das Projekt in einer Phase sehr hoher Arbeitsbelastung in den öffentlichen Arbeitsagenturen, die zu einer drastischen Reduzierung der Kapazitäten für die Einzelbera-tung von Arbeitslosen führte. Grundlage bildete ein Abkommen zwischen Gewerkschaftsverbänden und der schwedischen Arbeitsverwaltung. Basierend auf Geschäftsdaten der Arbeitsverwaltung untersucht dieses Papier die Wirkung des Projektes auf die Wahrscheinlichkeit aus der Arbeitslosenstatistik der Beschäftigungs-agenturen auszuscheiden (einzelne Gründe für das Ausscheiden werden separat untersucht) oder in ein Beschäftigungsprogramm aufgenommen zu werden. Für arbeitssuchende Pro-grammteilnehmer untersucht die Studie auch die Wahrscheinlichkeit des Eintritts in Beschäftigung im Anschluss an die Programmteilnahme. Ebenso wird der zeitliche Zusam-menhang zwischen dem Projektbeginn bis zum Ausscheiden eines Arbeitssuchenden aus der Arbeitslosenstatistik oder dessen Eintritt in ein Arbeitsmarktprogramm untersucht. Die Ergebnisse zeigen, dass sich das Projekt positiv auf die Bemühungen bei der Suche nach einer Beschäftigung auswirkt und dadurch Langzeitarbeitslosigkeit reduziert wird.
Keywords: 330; Arbeitsvermittlung; Arbeitsuche; Arbeitslosigkeit; Projektbewertung; Deutschland